Non-Equilibrium Particle Dynamics - Kim, Albert S. (IntechOpen, 2019)
All engineering processes are processes of non-equilibrium because one or all of heat, mass, and momentum transfer occur in an open system. The pure equilibrium state can be established in an isolated system, in which neither mass nor heat is transferred between the system and the environment. Most engineering transport analyses are based on the semi-, quasi-, or local equilibrium assumptions, which assume that any infinitesimal volume can be treated as a box of equilibrium. This book includes various aspects of non-equilibrium or irreversible statistical mechanics and their relationships with engineering applications. I hope that this book contributes to expanding the predictability of holistic engineering consisting of thermo-, fluid, and particle dynamics.